2023
DOI: 10.1097/mou.0000000000001100
|View full text |Cite
|
Sign up to set email alerts
|

Nerve-sparing technique in RPLND for testicular cancer

Abstract: Purpose of reviewThe management of testicular cancer has evolved over time with multimodal therapy. Retroperitoneal lymph node dissection (RPLND), which is a complex and potentially morbid treatment option, remains the mainstay in surgical treatment. This article reviews the surgical template, approach and anatomical considerations with regards to nerve spare in RPLND. Recent findingsThe standard full bilateral RPLND template has evolved over time to include the area between the renal hilum, bifurcation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In addition, Matos et al stated that non-nerve-sparing techniques showed important issues of fertility [114][115][116]. Another important issue regarding surgery is erectile dysfunction; contrary to what can be hypothesized, Dimitropoulos et al showed that in 53 patients, no difference in erectile functioning before and after operation was found [5].…”
Section: Sexual Dysfunction After Rplndmentioning
confidence: 99%
“…In addition, Matos et al stated that non-nerve-sparing techniques showed important issues of fertility [114][115][116]. Another important issue regarding surgery is erectile dysfunction; contrary to what can be hypothesized, Dimitropoulos et al showed that in 53 patients, no difference in erectile functioning before and after operation was found [5].…”
Section: Sexual Dysfunction After Rplndmentioning
confidence: 99%